CRP-cAMP mediates silencing of Salmonella virulence at the post-transcriptional level. - Youssef El Mouali; Tania Gaviria-Cantin; María Antonia Sánchez-Romero; Marta Gibert; Alexander J Westermann; Jörg Vogel; Carlos Balsalobre (PLoS Genetics, 2018)
Invasion of epithelial cells by Salmonella enterica requires expression of genes located in the pathogenicity island I (SPI-1). The expression of SPI-1 genes is very tightly regulated and activated only under specific conditions. Most studies have focused on the regulatory pathways that induce SPI-1 expression. Here, we describe a new regulatory circuit involving CRP-cAMP, a widely established metabolic regulator, in silencing of SPI-1 genes under non-permissive conditions. In CRP-cAMP-deficient strains we detected a strong upregulation of SPI-1 genes in the mid-logarithmic growth phase. Genetic analyses revealed that CRP-cAMP modulates the level of HilD, the master regulator of Salmonella invasion. This regulation occurs at the post-transcriptional level and requires the presence of a newly identified regulatory motif within the hilD 3'UTR. We further demonstrate that in Salmonella the Hfq-dependent sRNA Spot 42 is under the transcriptional repression of CRP-cAMP and, when this transcriptional repression is relieved, Spot 42 exerts a positive effect on hilD expression. In vivo and in vitro assays indicate that Spot 42 targets, through its unstructured region III, the 3'UTR of the hilD transcript. Together, our results highlight the biological relevance of the hilD 3'UTR as a hub for post-transcriptional control of Salmonella invasion gene expression.